Nephroprotective Effects of Polydatin against Ischemia/Reperfusion Injury: A Role for the PI3K/Akt Signal Pathway. (20th October 2015) - Liu, Hong-Bao; Meng, Qiu-Hong; Huang, Chen; Wang, Jian-Bo; Liu, Xiao-Wei
Abstract : Oxidative stress and inflammation are involved in the pathogenesis in renal ischemia/reperfusion (I/R) injury. It has been demonstrated that polydatin processed the antioxidative, anti-inflammatory, and nephroprotective properties. However, whether it has beneficial effects and the possible mechanisms on renal I/R injury remain unclear. In our present study I/R models were simulated both in vitro and in vivo . Compared with vehicle control, the administration of polydatin significantly improved the renal function, accelerated the mitogenic response and reduced cell apoptosis in renal I/R injury models, strongly suppressed the I/R-induced upregulation of the expression of tumor necrosis factor- α, interleukin-1 β, cyclooxygenase-2, inducible nitric oxide synthase, prostaglandin E-2, and nitric oxide levels, and dramatically decreased contents of malondialdehyde, but it increased the activity of superoxide dismutase, glutathione transferase, glutathione peroxidase and catalase, and the level of glutathione. Further investigation showed that polydatin upregulated the phosphorylation of Akt in kidneys of I/R injury dose-dependently. However, all beneficial effects of polydatin mentioned above were counteracted when we inhibited PI3K/Akt pathway with its specific inhibitor, wortmannin. Taken together, the present findings provide the first evidence demonstrating that PD exhibited prominent nephroprotective effects against renal I/R injury by antioxidative stress and inflammation through PI3-K/Akt-dependent molecular mechanisms.